Nostalgia in the Digital Age: Tanjleb Screen (2007- 2024) and its impact on Purbalingga Community - Dewi Naila Farichatul Izza; Muzakki Bashori (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Layar Tanjleb, the flagship program of the Purbalingga Film Festival (FFP) since 2007, offers an alternative form of entertainment resembling traditional open-air cinema. Initiated by Bowo Leksono, a former Jakarta journalist and founder of the Cinema Lovers Community (CLC), the program aims to promote film culture in Purbalingga. Its first film, “Orang Buta dan Penuntunnyaâ€ (2004), sparked mobile film screenings for high school students starting in 2005. Layar Tanjleb organizes free open-air screenings, showcasing fiction and documentary films by young directors, including works in the local Javanese Ngapak dialect. This study explores the evolution of Layar Tanjleb as a digital-era form of entertainment and its impacts on the creative economy as well as socio-cultural aspects. Using historical methods (heuristics, source criticism, interpretation, historiography) combined with interviews, observations, and literature review, the research demonstrates how Tanjleb strengthens local identity. The findings reveal that, to date, Tanjleb has screened 858 films and reached more than 135,000 viewers. The program has proven effective in reinforcing community bonds, promoting cultural pride, and stimulating growth. Layar Tanjleb is not merely entertainment, but also a medium of cultural education, local identity promotion, and a driving force of the creative economy ecosystem in Purbalingga.